Suburban Sahibs : three immigrant families and their passage from India to America - Kalita, S. Mitra, 1976- (Rutgers University Press, 2003)
"This book sheds new light on the pursuit of the American dream for the estimated 1.7 million Indians living in the United States. Suburban Sahibs delves into how immigration has altered the American suburb, and how the suburb, in turn, has altered the immigrant." "America has long been a destination for newcomers seeking better lives. In recent years, immigration by South Asians to the United States has increased dramatically, doubling between the 1990 and 2000 censuses. Unlike most of the European immigrants of the last century, however, many South Asians are moving directly to the suburbs rather than settling in large cities." "S. Mitra Kalita focuses on three waves of modern-day immigration through the stories of three families: the Kotharis, Patels, and Sahibs. Readers learn why these families decided to leave India, experience the tensions they encountered upon their arrival in the U.S. and witness the realities of life here for South Asians."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved